UNUSUAL CATCH OF GHOL PSEUDOSCIAENA DIACANTHUS OFF GOA - Thomas, P A; Kunju, M M (Indian Journal of Fisheries, 2011)
O.n 19th September 1973, a huge shoal of ’Ghol’ was caught by a private purse seiner off Goa. The total number of specimens captured was 2309 and the size ranged from 95 to 130 cm. with an average length of 109 cm. The total weight of the catch was estimated at 30.24 tonnes and composed of V to VII year old fish. Examination of stomach contemts revealed that the food item was Malabar Sole Cynoglossus macrostomiis (Norman). Regurgitated food was found inside the mouth, but extroverted stomach were not noted. The availability of food in the inshore waters off Goa is suggested as the prime factor in the inshore migration of "Ghol’ during the monsoon months.